The FEI3 readout chip for the ATLAS pixel detector - Perić, Ivan; Blanquart, Laurent; Comes, Giacomo; Denes, Peter; Einsweiler, Kevin; Fischer, Peter; Mandelli, Emanuele; Meddeler, Gerrit (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2006)
The latest pixel readout chip FEI3 for the ATLAS detector has been implemented in a standard 0.25 μ m CMOS process using radiation tolerant layout rules. It contains 2880 readout channels with densely packed analogue and digital circuits, a novel analogue front end and a complex time stamp based readout architecture and meets all specifications. Radiation tolerance has been demonstrated up to 100 Mrad of total dose. This paper summarizes the overall chip architecture and describes the most important circuit elements in some detail.